Socially in Action-Peers (SAp): Validation by Means of Confirmatory Factor Analysis (CFA) and Similarity Structure Analysis (SSA) - Rocha, A. (2014)
This study aimed to demonstrate the value and psychometric qualities of an instrument that assesses social competence for children in critical social situations within the relationships with peers in the school context - Socially in Action-Peers (SAp) using CFA and SSA. This instrument was administered to 182 Portuguese children aged between 8 and 11 years, of 3rd and 4th grades. These children were assessed by three sources: themselves, their peers and their teacher. Additionally, we used the Test of Emotion Comprehension (Pons & Harris, 2002; Pons, Harris & Rosnay, 2004) to assess SAp’s criterion-related validity. Mean differences results in SAp by gender were analyzed. Concerning to gender, we only have found gender significant differences in a few items and in the general assessment made by teachers, in which girls being considered superior. The results of the SAp’s psychometric analysis are satisfactory, both in terms of items’ sensitivity and reliability (internal consistency) in three versions (self-assessment, peer and teacher). Finally, we performed a confirmatory factor analysis that confirmed that the model underlying the instrument’s rational: a hierarchical model with a 1st order factor (composite social competence) that has three factors of 2nd order (consisting of the three sources of evaluation: self, peers and teacher). Besides the CFA data were analyzed through Louis Guttman’s SSA - a non-metric multidimensional scaling (MDS) procedure. CFA and SSA confirmed the psychometric qualities of SAp and identified the subscales and dynamic relationships between them. Implications of these findings for social competence assessment and intervention in childhood are discussed, as well as, the advantages and disadvantages of CFA compared to SSA for empirical validation of psychological constructs are examined.